A INTELIGÊNCIA ARTIFICIAL E O ENSINO DE LINGUAGENS: DESAFIOS E POSSIBILIDADES DE LETRAMENTO DIGITAL - Annaldina Lucas Pelzl (2022)
Living with a high quality of life, especially maintaining one’s mental health, in a society where technology is gradually replacing many of the human activities in the execution of multiple tasks and imposing a frenetic, liquid, and often hostile rhythm, has been challenging for human existence. In this context, one of the technologies that has advanced the most is Artificial Intelligence (AI). AI is being installed in different areas with the aim of simplifying people's daily lives, imposing a surprising speed, which human beings are having a hard time keeping up with and even mastering, as human beings usually do in the survival chain. In education, AI is increasingly a subject to be put forth and discussed, especially in the language teaching field, since it is the field most concerned with the language that circulates and shapes the individual in society. Within this context, human beings are being subjected to social needs that require the development of skills that provide them with the competence necessary to deal with AI, but they know little or almost nothing about the dimension in which this technology operates. Given this condition imposed by AI, I seek to organize the scope of my research based on literature already produced on the subject, relating it to theories on literacy and multiliteracies, with the aim of analyzing, discussing, and proposing that this topic be an object of teaching as a language, means of communication, and intervention in society. Initially, in the study, I present a conceptual overview of AI, focusing on some of its definitions (artificial neural networks, algorithms, learning systems) and characteristics (simulating human capabilities linked to intelligence: reasoning, perception of the environment and analysis skills for decision making), as well as literacies from theorists: Bostrom (2018); Lévy (2018); Russel and Norvig (2013); Santaella (2007); Teixeira (2015); Coscarelli (2017); Monte Mór (2017, 2018); Ribeiro (2021); Rojo (2013, 2015); Street (2014) among others. Thus, based mainly on the field of studies in Critical Applied Linguistics, I used a qualitative, exploratory, and literature review for this study. Based on this choice of research, I discuss concepts of AI, literacies, society, and more. I relate AI as being a form of language that can be studied through approaches to literacies and multiliteracies and consider how it is necessary to promote competencies and skills to deal with cyberspace and to be inserted in cyberspace culture. Therefore, I attempt to highlight that AI is multidisciplinary and has a line of study that foresees AI as a technology with learning potential, therefore it is an actant, and this implies providing teaching that helps human beings, whether in the condition of school education or not, to expand the dimension of learning itself, taking notice of its otherness and responsiveness. Keywords: Artificial Intelligence (AI). Literacies. Language teaching.